Automated Bonding Analysis with Crystal Orbital Hamilton Populations. Issue 11 (10th August 2022) - George, Janine; Petretto, Guido; Naik, Aakash; Esters, Marco; Jackson, Adam J.; Nelson, Ryky; Dronskowski, Richard; Rignanese, Gian‐Marco; Hautier, Geoffroy
Abstract: Invited for this month′s cover are researchers from Bundesanstalt für Materialforschung und ‐prüfung (Federal Institute for Materials Research and Testing) in Germany, Friedrich Schiller University Jena, Université catholique de Louvain, University of Oregon, Science & Technology Facilities Council, RWTH Aachen University, Hoffmann Institute of Advanced Materials, and Dartmouth College. The cover picture shows a workflow for automatic bonding analysis with Python tools (green python). The bonding analysis itself is performed with the program LOBSTER (red lobster). The starting point is a crystal structure, and the results are automatic assessments of the bonding situation based on Crystal Orbital Hamilton Populations (COHP), including automatic plots and text outputs. Coordination environments and charges are also assessed. More information can be found in the Research Article by J. George, G. Hautier, and co‐workers . Abstract : Automated bonding analysis software has been developed based on Crystal Orbital Hamilton Populations to facilitate high‐throughput bonding analysis and machine‐learning of bonding features. Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.202200123 ).